2011
DOI: 10.1086/658332
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Influence of Test Characteristics on the Clinical and Cost Impacts of Methicillin-ResistantStaphylococcus aureusScreening Programs in US Hospitals

Abstract: All screening options showed reductions in infection rates and cost impact improvement over no screening program. Among the options, same-day PCR testing for high-risk patients slightly edges out the others in terms of fewest infections and greatest potential cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
0
11
0
4
Order By: Relevance
“…3,4 The fundamental dilemma is that the costs of hospital-based screening and isolation are borne by the individual hospital performing the screening, but the individual benefits of screening may be reaped only later or by external beneficiaries (eg, other hospitals or non-hospital-based care entities). We suggest that the payment and incentive structure in the US system should be changed to support the expenditures necessary for infection prevention programs to realize both local and regional benefit.…”
Section: Reply To O'riordan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The fundamental dilemma is that the costs of hospital-based screening and isolation are borne by the individual hospital performing the screening, but the individual benefits of screening may be reaped only later or by external beneficiaries (eg, other hospitals or non-hospital-based care entities). We suggest that the payment and incentive structure in the US system should be changed to support the expenditures necessary for infection prevention programs to realize both local and regional benefit.…”
Section: Reply To O'riordan Et Almentioning
confidence: 99%
“…7 In hospitals where MRSA is endemic, screening (targeted or universal) reduced infection rates and was cost saving compared with a policy of no screening. 3,4 Universal MRSA screening strategies were more effective but also more cost-intensive than targeted screening. 4,6,7 In a retrospective review of a 3-year MRSA screening program that was implemented from 2006 to 2009 in the United Kingdom, only 7 extra MRSA cases were detected using universal screening compared with targeted screening, and in 1 month, universal screening generated 4,200 negative screens that incurred an additional €25,488 in laboratory costs.…”
mentioning
confidence: 99%
“…Prediction rules, [34][35][36] cost-efficiency analyses 37,38 and reviews 8,39 regarding universal surveillance for AROs have been performed primarily in the adult population. Cost-efficacy data for surveillance cultures for neonates are limited.…”
Section: © 2013 Lippincott Williams and Wilkinsmentioning
confidence: 99%
“…178-181 Although more costly than culture-based techniques, one potential advantage of these molecular tests is their ability to provide a result in less than 2 hours from the time of specimen collection, although in actual practice the turnaround time may be longer due to batching of samples. Although at least one uncontrolled study 182 and 3 mathematical models [183][184][185] have suggested that rapid testing may allow for more effective use of isolation precautions and enhanced prevention of MRSA transmission, a cluster-randomized crossover trial of universal screening in general wards failed to identify a difference in MRSA acquisition rates with the use of rapid testing compared with the use of a culture-based method. 186…”
Section: Appendix Strategies For Implementation Of An Mrsa Ast Programmentioning
confidence: 99%